Potential Analysis of Boat Lily Leaf Extract (Rhoeo spathaceae (Sw.) Stearn) as an Alternative Indicator in Acid-Base Titration of Acid-Base Learning - Muhamad Aditya Hidayah; Retno Aliyatul Fikroh (Postgraduate, University of Mataram, 2023)
The acid-base titration experiments at Senior High Schools typically use phenolphthalein and methyl orange indicators, which are relatively expensive and harmful to the environment. One of the plants containing anthocyanin pigments is boat lily (Rhoeo spathaceae (Sw.) Stearn) leaves. The research aims to determine the potential analysis of boat lily leaf extract as an alternative indicator used in chemistry learning in titration acid-base learning. The type of research used in this study is descriptive qualitative. Based on the research and discussion results, the pedagogical aspects carried out by chemistry teachers obtained results that using boat lily leaf extract indicators in acid-base titration in the acid-base chapter is appropriate and meets pedagogical terms to be applied by chemistry teachers. A review of chemistry teachers, laboratory employees, and students obtained results that the use of boat lily leaf extract indicators in acid-base titration in the acid-base chapter can be approved because it meets the aspects of ease to be applied in learning, understanding, and attractive to students, and ease of being provided in the laboratory. Based on the feasibility analysis of potential experiments, boat lily leaf extract is feasible based on financial aspects and shelf life resilience.